2013
DOI: 10.56431/p-q38442
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Optical Characterization of ZnO Nanoparticles Synthesized by Microemulsion Route

Abstract: ZnO nanoparticles were synthesized by microemulsion route in W/S ratio of 5 at room temperature. X-ray diffraction (XRD) pattern reveals wurtzite structure of ZnO nanoparticles. Rod shape of ZnO nanoparticles of average particle size 10.0 to 12.0 nm were observed by transmission electron microscopy. FT-IR spectra confirmed the adsorption of surfactant molecules at the surface of ZnO nanoparticles and presence of Zn-O bonding. Thermal studies were carried out by the differential scanning calorimeter (DSC) techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(35 citation statements)
references
References 27 publications
7
27
1
Order By: Relevance
“…In addition, the peak of 1267.29 cm -1 suggests the presence of a C-O group, and the peak of 708 cm -1 denotes the presence of a ZnO functional group. Consistent with research[15] stated that metal oxide has a peak in the fingerprint area…”
supporting
confidence: 79%
“…In addition, the peak of 1267.29 cm -1 suggests the presence of a C-O group, and the peak of 708 cm -1 denotes the presence of a ZnO functional group. Consistent with research[15] stated that metal oxide has a peak in the fingerprint area…”
supporting
confidence: 79%
“…The second peak at ∼258.11 °C, showing a heat flow of −1.65 J/g, is due to the conversion of zinc chloride to zinc oxide nanostructures. After that, the reduction of the heat flow can be attributed to the conversion of zinc oxide into zinc nanostructures …”
Section: Resultsmentioning
confidence: 99%
“…This reaction is shown for amino acid present in protein biomolecules same reaction will happen for other biomolecules present in palash leaves powder, this amino acid & other functional groups present in biomolecules will be coated with ZnO nanoparticles to work as reducing and stabilizing agent SiO 2 was naturally present in palash leaves powder shown by EDX and FTIR of paalsh leaves powder [13][14][15] . The mechanism and role of biomolecules present in palash leaves are shown in Fig.…”
Section: Mechanism For Synthesis Of Zno/sio 2 Nanocatalyst By Palash ...mentioning
confidence: 97%
“…FTIR result is also showing stretching for Si-O-Si and in Zn-O, thus it has been confirmed that synthesized nanocatalystis ZnO/SiO 2 nanocomposite. From FTIR image, it can be said that ZnO stretching is found at IR frequency 492.83 and 1634.73 [13,18,20] . And for SiO 2, IR, frequency is found at 981.80 1028.09 and 1065.71 [20] .…”
Section: Ftir Analysismentioning
confidence: 99%